2010
DOI: 10.1128/jvi.02516-09
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Viremia and Production of Neutralizing Antibodies Differentially Regulated by PolymorphicAPOBEC3andBAFF-RLoci in Friend Virus-Infected Mice

Abstract: Several host genes control retroviral replication and pathogenesis through the regulation of immune responses to viral antigens. The Rfv3 gene influences the persistence of viremia and production of virusneutralizing antibodies in mice infected with Friend mouse retrovirus complex (FV). This locus has been mapped within a narrow segment of mouse chromosome 15 harboring the APOBEC3 and BAFF-R loci, both of which show functional polymorphisms among different strains of mice. The exon 5-lacking product of the APO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
70
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 55 publications
7
70
0
Order By: Relevance
“…Several studies have suggested that APOBEC BALB is less effective that APOBEC BL6 at restricting infection by F-MLV (27,30,50). However, clearly both alleles are important anti-M-MLV restriction factors, because reversion occurred with similar kinetics and frequency in the two mouse strains, and both alleles effectively inhibited reverse transcription in EnRT assays.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that APOBEC BALB is less effective that APOBEC BL6 at restricting infection by F-MLV (27,30,50). However, clearly both alleles are important anti-M-MLV restriction factors, because reversion occurred with similar kinetics and frequency in the two mouse strains, and both alleles effectively inhibited reverse transcription in EnRT assays.…”
Section: Discussionmentioning
confidence: 99%
“…1D, right panel). However, the average plasma number of F-MuLV genome was significantly (14). Each closed circle represents the actual value obtained from an individual mouse.…”
mentioning
confidence: 99%
“…Thus, AID-mediated SHM and CSR are not required for F-MuLV elimination. Plasma viremia and virus-neutralizing Ab were detected as described previously (14). While MT/MT mice remained viremic even at 16 weeks pi, AID Ϫ/Ϫ mice cleared viremia, albeit less quickly than the WT mice did (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations